2023
DOI: 10.1097/fjc.0000000000001484
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor TCF3 Promotes Macrophage-Mediated Inflammation and MMP Secretion in Abdominal Aortic Aneurysm by Regulating miR-143-5p/CCL20

Yuejin Li,
Rougang Li,
Yu Li
et al.

Abstract: Damage to the abdominal aortic wall and the local inflammatory response are key factors resulting in abdominal aortic aneurysm (AAA) formation. During this process, macrophage polarization plays a key role. However, in AAA, the regulatory mechanism of macrophages is still unclear, and further research is needed. In this study, we found that the transcription factor TCF3 was expressed at low levels in AAA. We overexpressed TCF3 and found that TCF3 could inhibit MMP and inflammatory factor expression and promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…CCND2 [814], VCAM1 [615], PDGFB (platelet derived growth factor subunit B) [795], PRKCB (protein kinase C beta) [780], ACTC1 [924], DAPK1 [947], hsa-mir-17-5p [1672], hsa-mir-2110 [1673], TCF3 [1674] and SMARCA4 [1675] are associated with developing cardiovascular diseases. CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…CCND2 [814], VCAM1 [615], PDGFB (platelet derived growth factor subunit B) [795], PRKCB (protein kinase C beta) [780], ACTC1 [924], DAPK1 [947], hsa-mir-17-5p [1672], hsa-mir-2110 [1673], TCF3 [1674] and SMARCA4 [1675] are associated with developing cardiovascular diseases. CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%